2020
DOI: 10.1111/odi.13277
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microbiota and inflammation‐related proteins in patients with psoriasis

Abstract: Objective The purpose of the present study was to characterize the composition of the salivary microbiota and quantify salivary levels of inflammation‐related proteins (neutrophil gelatinase‐associated lipocalin [NGAL] and transferrin) in patients with psoriasis and compare data to those obtained in patients with periodontitis and orally healthy controls, respectively. Materials and methods Stimulated saliva samples from patients with psoriasis (n = 27), patients with periodontitis (n = 58), and orally healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Multiple explanations may account for these discrepancies, including the nature of the inflammatory molecules studied as well as the different clinical status of the participants in the two studies. Nevertheless, we have previously demonstrated significantly different transferrin levels in saliva in patients with periodontitis and healthy controls [ 27 ], which is why these were included in the present study. Future studies are needed to validate if the changes in transferrin levels could be interpreted as an indirect effect of the probiotic strains tested.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Multiple explanations may account for these discrepancies, including the nature of the inflammatory molecules studied as well as the different clinical status of the participants in the two studies. Nevertheless, we have previously demonstrated significantly different transferrin levels in saliva in patients with periodontitis and healthy controls [ 27 ], which is why these were included in the present study. Future studies are needed to validate if the changes in transferrin levels could be interpreted as an indirect effect of the probiotic strains tested.…”
Section: Discussionmentioning
confidence: 97%
“…Participants were briefed through video, verbal and written instructions to collect two different saliva samples. First, a stimulated Salivette ® saliva sample was collected as described in our recent study [ 27 ], followed by a paraffin-stimulated saliva sample as previously described [ 33 ]. Thus, a minimum of 1 mL of stimulated saliva was collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could include factors like, gingivitis, periodontitis, inflammatory disease, salivary pH and viscosity, mucosal dryness, the composition and time since the last meal, to mention some. (Belstrom et al, 2020; Farnaud et al, 2010; Lynge Pedersen & Belstrom, 2019) Another way of achieving higher specificity could be repeated sampling. Oral mucosa has turnover rate of 4 hr and with proper cleansing this might make it possible to calculate NGAL delta values.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Belstrøm et al (2020) studied stimulated saliva samples from patients with psoriasis, patients with periodontitis and controls without oral lesions by means of NGS of the 16S rRNA gene. They found that some bacterial taxa differentiated the salivary microbiota in patients with psoriasis from that of patients with periodontitis and orally healthy controls.…”
Section: Oral Microbiome and Autoimmune Diseasesmentioning
confidence: 99%